ANALYSIS OF THE ROLE OF EMOTIONAL INTELLIGENCE INCREASING LEARNING MOTIVATION CRITICAL PEDAGOGIC PERSPECTIVE - Fian, Khafifatul; Roqib, Moh. (PT Altin Riset Publishing, 2025)
This paper aims to analyse the role of emotional intelligence in enhancing students' learning motivation from Daniel Goleman's perspective. The method used by the author is a literature review, collecting data from primary sources, particularly the book